Effects of organizational behavior and internal communication on the productive performance of a public telecommunications company in Algeria - Megheni, Zineb; Nedil, Lamia (Journal of Ecohumanism, 2026)
In a context of accelerated technological change and increasing economic volatility, public telecommunications companies play a central role, influencing organizational culture and management practices. The telecommunications sector has also had to contend with, and continues to contend with, the repercussions of the Covid-19 pandemic, which has disrupted operational dynamics globally. Despite these challenges, the telecom sector is demonstrating resilience and continuing to evolve. In this context, our attention focused on employee productivity. We conducted a field survey of staff at telecommunications sales agencies in Algeria, with a focus on the Algiers region. The central objective was to analyze the relationship between two key dimensions: (i) employee behavior towards customers and (ii) internal communication among colleagues, in order to identify levers likely to improve company productivity. Goals Measure the link between organizational behavior and customer satisfaction/relationship. Evaluate internal communication practices (information flow, feedback, transparency). Analyze the impact of these variables on productivity (efficiency, deadlines, quality of service) within the agencies studied.